Analisis Kegiatan Ice Breaking Pada Pembelajaran IPAS di SD Negeri Pengaradan 02 - Dhita Fajriyani Agustin; Laelia Nurpratiwiningsih; Didik Tri setiyoko (Journal on Education, 2024)
The purpose of this research is to examine the analysis of ice breaking activities in science lessons at SD Negeri Pengaradan 02. The main focus of this study is on how ice breaking activities are conducted in science classes at SD Negeri Pengaradan 02, the factors that influence and hinder the success of these activities. This research uses a qualitative descriptive approach by utilizing documentation, observation, and interviews as data collection methods. Analysis techniques such as data collection, editing, processing, and verification are used. The findings indicate that incorporating ice-breaking activities in science education can improve student learning outcomes by reducing dropout rates and increasing concentration. Common ice breakers used by teachers include songs, sports, and games held at the end or during breaks between classes. The implementation of ice breaking in science lessons can make students more engaged, confident, and cooperative during the learning process. However, in the process of implementing ice breaking, teachers must consider the classroom environment and students' learning styles to determine whether the activities can be carried out or not. Factors affecting ice breaking have the potential to streamline the learning process and make classes more interesting and enjoyable. The main benefit of ice breaking activities is the teacher's creative ability to explain the various types of ice breaking that occur in the classroom.